The spillover effect of advertising on the capital market: Evidence from financial constraints - Jiang, Fuxiu; Shen, Yanyan; Xia, Xiaoxue (Journal of Corporate Finance, 2024)
Firms are embedded in the product market as well as the capital market. Their behavior in the product market will inevitably affect their performance in the capital market, and vice versa. Using a sample of Chinese listed firms, we empirically test the existence of spillover effect of advertising on financial constraints in the capital market. We find that product market advertising significantly alleviates the firm's financial constraints, especially when the information asymmetry between insiders and outsiders is more serious and when the firm is in a consumer-product industry. We also find that advertising improves brand value, increases attention, and alleviates peer firms' financial constraints, providing supplementary evidence that one alleviation mechanism is information asymmetry. Further analyses show that advertising significantly reduces the firm's financing costs. These findings provide valuable insights into how firms alleviate financial constraints.